Evolution of international environmental regimes : the case of climate change - Schiele, Simone (Cambridge studies in international and comparative law ;)
"Drawing specifically on the international climate regime, Simone Schiele examines international environmental regimes from a legal perspective and analyses a core feature of international regimes - their ability to evolve over time. In particular, she develops a theoretical framework based on general international law which allows for a thorough examination of the understanding of international law and the options for law-creation in international environmental regimes. The analysis therefore provides both a coherent understanding of the international climate regime and a starting point for further research in other regimes"--